Satisfaction with Distance Learning in the post-COVID Era as influenced by Learning Environment, Technological Glitches and Course Content in Undergraduate Dental Education - MUMCU, GONCA; AKMANSOY, ŞÜKRÜ CAN; ŞİŞMAN KİTAPÇI, NUR; KİTAPÇI, OKAN CEM (My University, 2022)
Aim: This study aimed to evaluate learner satisfaction related to the components of Distance Learning (DL) by using mediation analysis in dental students. Methods: In this study, 608 dental students were included. Data were collected through the use of an online questionnaire. Results: In the multiple mediation analysis, the increase in “Satisfaction score with DL” was directly mediated by the Clinical students (p=0.0250) and indirectly mediated by the increase in the score of items concerning “Relating Theoretical Course to Clinical Practice” (p=0.0009)”, “Satisfaction with Course Content” (p=0.0000)” and “Comfortable learning environment” p=0.0000) in Clinical students whereas a poor score was associated with an elevated score of the item concerning “Technological glitches in live lectures” (p=0.0000)” in Preclinical students. Conclusions: Satisfaction with DL was associated with the students’ clinical experience as well as course content, the learning environment. Unsurprisingly technological glitches were associated with the overall experience of DL. Keywords: Distance learning; Learning Environment; Technological Glitches; Course Content; Dentistry
Keywords: Distance learning; Learning Environment; Technological Glitches; Course Content; Dentistry